The Indicator Test Neuropad in the Assessment of Small and Overall Nerve Fibre Dysfunction in Patients with Type 2 Diabetes: a Large Multicentre Study - Manes, C.; Papanas, N.; Exiara, T.; Katsiki, N.; Papantoniou, S.; Kirlaki, E.; Tsotoulidis, S.; Kefalogiannis, N.; Maltezos, E. (Experimental and Clinical Endocrinology & Diabetes, 2014)
We examined the diagnostic utility of the indicator test Neuropad in the assessment of overall and small fibre dysfunction in 1 010 patients with type 2 diabetes mellitus (T2DM) (608 men, mean age 63.9±10.3 years) from 5 diabetes clinics. Sudomotor function was diagnosed by the Neuropad® test. Overall and small nerve fibre dysfunction was diagnosed through clinical examination and symptoms. Patients were divided into Groups A (441 patients with sudomotor dysfunction) and B (569 patients without sudomotor dysfunction). The former were older (p<0.05) and had longer T2DM duration (p<0.05) than the latter. For overall nerve fibre dysfunction, abnormal Neuropad defined as patchy/blue had 94.9% sensitivity, 70.2% specificity and 98.1% negative predictive value (NPV), while for small fibre dysfunction the corresponding values were 85.6%, 71.2% and 93.3%. For overall nerve fibre dysfunction, abnormal Neuropad defined as blue had 64% sensitivity, 96% specificity and 91% NPV, while for small fibre dysfunction the corresponding values were 52%, 96% and 85%. The odds ratios (ORs) of Neuropad patchy/blue for overall and for small fibre dysfunction were 43.7 and 14.7, respectively. The ORs of Neuropad blue for overall and for small fibre dysfunction were 45.7 and 24.9, respectively. In conclusion, Neuropad patchy/blue response exhibited better diagnostic performance both for overall and small nerve fibre dysfunction. Its very high NPV renders it an excellent screening tool primarily to exclude neuropathy in T2DM.
Keywords: diabetes mellitus; diabetic neuropathy; Neuropad; small fibre dysfunction; sudomotor dysfunction.